Pembinaan Rohani Warga Binaan Katolik di Lembaga Pemasyarakatan Narkotika Kelas IIA Samarinda - Yustinus Sanda; Simon Devung; Wilfridus Samdirgawijaya (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2020)
The research aims to view the Spiritual Guidance given to Catholic Prisoners at Lembaga Pemasyarakatan Narkotika Kelas IIA Samarinda by the Catholic Church. The research was conducted at Lembaga Pemasyarakatan Narkotika Kelas IIA Samarinda using qualitative descriptive methods and the data collection techniques used were interviews, observation, documentation and document study. The informants in this study were eight subjects. Based on the research results, the researcher found that the Catholic Prisoners at Lapas Narkotika Kelas IIA Samarinda did not get routine Spiritual Guidance from the Catholic Church. The Spiritual Guidance for Catholic Prisoners is carried by the Protestant Church. The Catholic Church so far has never done Spiritual Guidance for the Catholic Prisoners at Lapas Narkotika. The Catholic Prisoners have only received Catholic Spiritual Guidance conducted by STKPK Bina Insan Samarinda in the form of Liturgy of the Word and by doctor Videlia Rosy Pakonglean in the form of Devotion to St. Mary.